Analysis of biofilm formation by Sporothrix schenckii. (14th May 2020) - Sánchez-Herrera, Rocío; Flores-Villavicencio, Lérida Liss; Pichardo-Molina, Juan Luis; Castruita-Domínguez, José Pedro; Aparicio-Fernández, Xochilt; Sabanero López, Myrna; Villagómez-Castro, Julio Cesar
Abstract: The development of mature biofilms is an aid in numerous aspects of the life cycle of fungi. It is well known that Sporothrix schenckii complex causes a benign subcutaneous mycosis, but recent studies have suggestedthat biofilm formation may be one of the important factors involved in its virulence. Here we report the study of the biomass organization and a model of the stages of S. schenckii biofilm development: adsorption, active adhesion, microcolony formation, maturation, and dispersal of biofilm fragments. During the development, the biofilm is surrounded by extracellular matrix, which contains glycoprotein (mannose rich), carbohydrates, lipids, and nucleic acid. In addition, the extracellular DNA increases in extracellular matrix as a key component to structural integrity and antifungal resistance. The study of S. schenckii biofilm contributes to a better understanding of growth biofilm and physiology, adding new insights into the mechanisms of virulence and persistence of pathogenic microorganisms.